2000
DOI: 10.1111/j.1572-0241.2000.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Cytokine Production in Radiation-Induced Proctosigmoiditis Compared With Inflammatory Bowel Disease

Abstract: The mucosal levels of IL-2, IL-6, and IL-8 were significantly higher in both diseased and normal segments of colon in patients with radiation proctitis, compared with normal controls. Only IL-1beta levels were significantly higher in diseased segments, compared with endoscopically normal-appearing segments in radiation proctitis. These results indicate that there is a similarity in the activation of mucosal cytokines between IBD and radiation proctosigmoiditis. This may partly explain the beneficial effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 11 publications
0
46
0
3
Order By: Relevance
“…Radiation-induced tissue damage in humans was shown to be associated with elevated levels of interleukin 2 (IL-2), IL-6, IL-8 and particularly IL-1β 4. We have previously shown that IL-1β was also most closely correlated with tissue injury in a mouse radiation proctitis (RP) model 5…”
Section: Introductionmentioning
confidence: 99%
“…Radiation-induced tissue damage in humans was shown to be associated with elevated levels of interleukin 2 (IL-2), IL-6, IL-8 and particularly IL-1β 4. We have previously shown that IL-1β was also most closely correlated with tissue injury in a mouse radiation proctitis (RP) model 5…”
Section: Introductionmentioning
confidence: 99%
“…Tumor necrosis factor-alpha (TNF-α) levels are also significantly elevated in irradiated mice compared with non-irradiated controls [5] . These data may partially explain the beneficial effects of similar systemic and topical drugs including mesalamine compounds and steroids when used in radiation-induced proctosigmoiditis [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) is suggested to play a significant role in intestinal inflammation [11, 12] andIL-6 reflects the degree and extent of disease activity [13] with a closer correlation between IL-6 and active disease in pediatric UC patients than CD patients [14,15,16]. …”
Section: Introductionmentioning
confidence: 99%